Lessons from the coronavirus disease 2019 pandemic: Will virtual patient management reshape uro-oncology in Germany?. (June 2020) - Rodler, Severin; Apfelbeck, Maria; Stief, Christian; Heinemann, Volker; Casuscelli, Jozefina
Abstract: The coronavirus disease 2019 (COVID-19) pandemic is challenging for physicians treating patients with genitourinary cancers as they are considered at high risk of severe events. The uro-oncology outpatient clinic at our academic institution was affected early by the outbreak owing to the widespread infection of healthcare personnel. Subsequently, we developed a strategy to ensure the patient's safety by efforts focused on strict quarantine observation, reduction of clinic visits and implementation of virtual patient management into the workflow. Furthermore, we analysed susceptibility to COVID-19 and its effects on patients with uro-oncological cancer treated with antitumoural agents. The goal is to warrant high-quality cancer care, despite being an academic centre on the front line of Germany's response to COVID-19. Highlights: The coronavirus disease 2019 changes the management of genitourinary cancers. Telehealth and treatment in less exposed care settings are important strategies. Implementation of telehealth might impact cancer care after the pandemic in Germany.